2014
DOI: 10.1186/1471-2407-14-402
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and prognostic implications of NOK/STYK1 protein expression in non-small cell lung cancer

Abstract: BackgroundThe expression of novel oncogenic kinase (NOK), a member of the protein tyrosine kinase (PTK) family, has been observed in several human malignancies including non-small cell lung cancer (NSCLC). However, the clinic relevance of NOK expression in NSCLC remains unclear.MethodsIn this study, NOK expression in tumor cells was assessed using immunohistochemical methods in 191 patients with resected NSCLC. The association of NOK expression with clinicopathological parameters, including the Ki-67 labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Our own previous studies have demonstrated that the overexpression of NOK is significantly associated with lymphatic metastasis in NSCLC. 12 However, the relationship between NOK and EMT has not yet been elucidated and fully defined mechanistically. In this study, we verify that NOK has a tumorigenic activity and may correlate with tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own previous studies have demonstrated that the overexpression of NOK is significantly associated with lymphatic metastasis in NSCLC. 12 However, the relationship between NOK and EMT has not yet been elucidated and fully defined mechanistically. In this study, we verify that NOK has a tumorigenic activity and may correlate with tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The K-M survival analysis revealed that patients with high NOK expression (median survival time: 12.0 months) showed a trend of shorter OS than those of low NOK expression (median survival time: 19.5 months, P=0.0790; Supplementary Figure 1), which was consistent with our previous study. 12 The association between NOK expression and the clinicopathological variables was analyzed (…”
Section: The Upregulated Expression Of Nok In Human Nsclc Tissues Is mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prognostic and therapeutic significance of STYK1 overexpression in human malignant diseases has also been revealed. Chen P et al recently demonstrated that increased expression of STYK1 protein correlates with poor prognosis of patients with non-small cell lung cancer [ 17 ]. Nirasawa S et al provided evidence that STYK1 is a novel drug resistance factor and could be a potential predictor of the therapeutic response in acute leukemia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…All stained sections were examined by two independent investigators who were blinded to the clinical features and outcomes. The immunohistochemical (IHC) staining scores were based on the following criteria: (i) the percentage of positive cells (0, ≤5%; 1, 6%‐25%; 2, 26%‐50%; 3, 51%‐75%; and 4, >75%); (ii) the staining intensity (0, no color; 1, yellow; 2, brown; and 3, tan); and (iii) the two grades were multiplied together and specimens were assigned to one of four levels: 0, negative (−); 1‐4, weakly positive (+); 5‐8, moderately positive (++); and 9‐12, strongly positive (+++) . To investigate the correlation of protein expression, (−) and (+) were considered as low expression, and (++) and (+++) were considered as high expression.…”
Section: Methodsmentioning
confidence: 99%